The Role of Anthologies in Developing Approaches to The Study of Asian American Literature - Мащенко, Олена Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article reviews the role and position of the first anthologies of American literature written by writers of Asian descent, due to which the outlines for what are now commonly known as Asian American literary studies were defined. A close analysis of these anthologies enables to realize why the existence of a unified collective Asian American identity, which was proclaimed in the second half of the 20th century, is being questioned at the milestone of the 20th and 21st centuries. It gives reason to state that the anthologies did not only emphasize the status quo of literature created by American writers of Asian descent, but also formed fracture lines along which at the end of the 20th century efforts were made to deprive Asian-American literature of the status of marginal, secondary and present it as a full-fledged component of American literary continuum. The first one can be described as “beyond the hyphen”. The second trajectory of the search for a way out of ethnic shelter at the end of the 20th century is aimed at “reconfiguring the canon”. It involves not only a demand of being fully involved into the American literary tradition, but also a search for its role in shaping, if not generating contemporary American literature. The anthologies that hold the primacy in the discovery of American writers of Asian descent, as a literary fact on one side, were both a continuation and rethinking of the tradition of Eastern (Chinese/Japanese) anthologies. On the other hand, despite the extremely compressed theoretical foundation for the essence of this wing of American literature, they show the extent and dynamism of its understanding and interpretation as an integral part of Western literary discourse.